Screening and Isolation of Cyclodextin Glucanotransferase Producing Fungi From Selected UNIMAS AAS Collection - Amirah, Ahmad (Universiti Malaysia Sarawak, UNIMAS, 2010)
Cyclodextrin (CDs) is a cyclic homogenous oligosaccharide, synthesized from starch by an enzyme called cyclodextrin glucanotransferase (CGTase, EC 2.4. 1. 19) via a process called intramolecular transglycosylation in microorganism. CGTase is produced mainly by bacteria and recent finding shows that archae is also able to produce CGTase. However, there is no study conducted on fungi to determine its potential as CGTase producer. Screening of CGTase producing fungi was done on samples obtained from UNIMAS AAS fungi collection. Rapid screening was done by using Horikoshi media with phenolphthalein and methyl orange. Sample SW005 which is Aspergillus sp. showed the best CGTase activity during screening compared to other sample as well as having the highest enzyme activity based on phenolphthalein assay which measure β-CD forming activity.